An analysis of national action plans on antimicrobial resistance in Southeast Asia using a governance framework approach - Alvin Qijia Chua; Monica Verma; Li Yang Hsu; Helena Legido-Quigley (The Lancet Regional Health. Western Pacific, 2021)
Summary: The complex problem of antimicrobial resistance (AMR) is spread across human health, animal health, and the environment. The Global Action Plan (GAP) on AMR and context-specific national action plans (NAPs) were developed to combat this problem. To date, there is no systematic content analysis of NAPs from countries of the Association of Southeast Asia Nations (ASEAN). As the validity periods of most NAPs are ending, an analysis now will provide an opportunity to improve subsequent iterations of these NAPs. We analysed the current NAPs of ten ASEAN countries. We explored their objective alignment with GAP and performed content analysis using an AMR governance framework. Themes were broadly classified under five governance areas: policy design, implementation tools, monitoring and evaluation, sustainability, and One Health engagement. We identified policy priorities, useful features of NAPs, and specific areas that should be strengthened, including accountability, sustained engagement, equity, behavioural economics, sustainability plans and transparency, international collaboration, as well as integration of the environmental sector. Enhancement of these areas and adoption of best practices will drive improved policy formulation and its translation into effective implementation.